Lack of species-specificity in mammalian sperm chemotaxis - Sun, Fei (2003)
Attraction of spermatozoa by way of chemotaxis to substances secreted from the egg or its surrounding cells has been demonstrated in marine species, amphibians, and mammals. This process is species- or family-specific in marine invertebrates: a chemoattractant for one marine species is usually not recognized by another species or by a member of another family. It is not known whether this selectivity is also the rule in other phyla. Furthermore, it is not at all obvious that such selectivity would be advantageous to species with internal fertilization. Here, using a directionality-based assay for chemotaxis, we studied in vitro the chemotactic response of human and rabbit spermatozoa to human, rabbit, and bovine egg-related factors. We found that spermatozoa from each of the two sources responded similarly well to egg-related factors obtained from any of the three species examined. These results indicate lack of chemotaxis-related, species specificity between these species, suggesting that their sperm chemoattractants are common or very similar. The findings further suggest that mammals do not rely on species specificity of sperm chemotaxis for avoidance of interspecies fertilization. © 2003 Elsevier Science (USA). All rights reserved.